2017
DOI: 10.1037/abn0000307
|View full text |Cite
|
Sign up to set email alerts
|

The social transmission of risk: Maternal stress physiology, synchronous parenting, and well-being mediate the effects of war exposure on child psychopathology.

Abstract: While chronic early stress increases child susceptibility to psychopathology, risk and resilience trajectories are shaped by maternal social influences whose role requires much further research in longitudinal studies. We examined the social transmission of risk by assessing paths leading from war-exposure to child symptoms as mediated by 3 sources of maternal social influence; stress physiology, synchronous parenting, and psychiatric disorder. Mothers and children living in a zone of continuous war were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 163 publications
1
45
0
Order By: Relevance
“…Children's social engagement is an orientation maturing on the basis of biological dispositions integrated with sensitive parenting, shows individual stability over time, and predicts social competencies with peers (Feldman & Masalha, ). We found that among children growing in war‐zones, social engagement mediated the effects of trauma on child behavior problems at 10 years, similar to the current findings (Halevi et al., ). Possibly, by school‐age, children's social skills and engaged versus withdrawn style play an important role in resilience, enabling children to draw comfort from their peers and to create meaningful attachments.…”
Section: Discussionsupporting
confidence: 91%
“…Children's social engagement is an orientation maturing on the basis of biological dispositions integrated with sensitive parenting, shows individual stability over time, and predicts social competencies with peers (Feldman & Masalha, ). We found that among children growing in war‐zones, social engagement mediated the effects of trauma on child behavior problems at 10 years, similar to the current findings (Halevi et al., ). Possibly, by school‐age, children's social skills and engaged versus withdrawn style play an important role in resilience, enabling children to draw comfort from their peers and to create meaningful attachments.…”
Section: Discussionsupporting
confidence: 91%
“…The infant's oxytocin system is shaped by caregiving. Animal studies indicate that maternal behavior programs oxytocin receptor availability in the brain 71 , and longitudinal human studies show that peripheral oxytocin is programmed by sensitive parenting repeatedly experienced throughout childhood 72‐74 . Oxytocin induces a physiological state of quiescence that affords participation in the world without fear and stimulates the desire for social contact through its links with dopamine in striatal neurons 75‐77 .…”
Section: Core Components Of the Neurobiology Of Affiliationmentioning
confidence: 99%
“…Although behaviors certainly play a role in coregulatory physiological processes, these may often be subtle or "hidden" behaviors, such as touch, gaze, smell, tone of voice, posture, gesture, or facial expression, which are not detectable using global observational or self-report measures, but may be more easily detected using physiological methods. Three recent studies provide support for this idea, having shown that the effects of stress exposure on a child's physiology were mediated by the mother's physiological stress (Halevi et al, 2017;Hibel & Mercado, 2017;Waters et al, 2014). Importantly, in all three studies, stress transmission was at least partially independent of observed measures of caregiving behavior, highlighting the significance of physiology as a more robust indicator of transmission.…”
Section: Maternal Stress Physiology As a "Hidden" Regulatormentioning
confidence: 84%
“…Three recent studies provide support for this idea, having shown that the effects of stress exposure on a child's physiology were mediated by the mother's physiological stress (Halevi et al, 2017;Hibel & Mercado, 2017;Waters et al, 2014). Three recent studies provide support for this idea, having shown that the effects of stress exposure on a child's physiology were mediated by the mother's physiological stress (Halevi et al, 2017;Hibel & Mercado, 2017;Waters et al, 2014).…”
Section: Maternal Stress Physiology As a "Hidden" Regulatormentioning
confidence: 91%